The Role of Intellectual Property Rights Protection on Intra- Comesa Trade with A Specific Focus on Trademarks - Masunda, Stein; Mhonyera, Gabriel (International Journal of Economics and Financial Issues, 2024)
This paper employs the Pseudo Poisson Maximum Likelihood estimation technique to investigate the impact of trademarks, as a proxy for Intellectual Property Rights (IPRs), on intra-Common Market for Eastern and Southern Africa (COMESA) trade using panel data from 2000 to 2022. While the study establishes significant aggregate-level market expansion effects of trademarks on imports within COMESA, it also reveals sector-specific variations. Specifically, the study confirms a positive correlation between trademark-related imports of plastics, pharmaceuticals, rubber, tobacco, paper, and footwear products, suggesting that stronger trademark enforcement could enhance market expansion in this sector. Conversely, a negative correlation between trademark-related imports of dairy and clothing products is exposed, indicating potential market power effects that might restrict intra-COMESA trade. These findings underscore the importance of tailored IPRs policies across sectors, advocating for strengthened trademark protection in sectors that are significant and positively affected, while suggesting a more lenient approach for promoting trade in negatively affected sectors within the COMESA region.